2019
DOI: 10.1002/lio2.267
|View full text |Cite
|
Sign up to set email alerts
|

Facial nerve venous malformation: A radiologic and histopathologic review of 11 cases

Abstract: Objective The purpose of this article was to provide a combined pathologic and radiologic review of previous pathologically diagnosed facial nerve “hemangiomas” to confirm that these lesions are most characteristic of venous malformations rather than neoplasms. Study Design Retrospective radiologic, clinical, and histopathologic review of all patients with a previous pathologically diagnosed facial nerve hemangioma of the temporal bone who underwent computed tomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…However, the traditional nomenclature that refers to the lesions as "hemangiomas" persists. Venous malformations consist of enlarged venous channels with a single flattened layer of endothelial cells, no appreciable mitotic figures, absent internal elastic lamina, and a smooth muscle component [Benoit et al, 2010;Guerin et al, 2019]. These features were not present in our samples, and neither did they present an organized morphology corresponding to a vascular tumor, in accordance with the current classification of the International Society for the Study of Vascular Anomalies [Wassef et al, 2015;Merrow et al, 2016].…”
Section: Pathologysupporting
confidence: 84%
“…However, the traditional nomenclature that refers to the lesions as "hemangiomas" persists. Venous malformations consist of enlarged venous channels with a single flattened layer of endothelial cells, no appreciable mitotic figures, absent internal elastic lamina, and a smooth muscle component [Benoit et al, 2010;Guerin et al, 2019]. These features were not present in our samples, and neither did they present an organized morphology corresponding to a vascular tumor, in accordance with the current classification of the International Society for the Study of Vascular Anomalies [Wassef et al, 2015;Merrow et al, 2016].…”
Section: Pathologysupporting
confidence: 84%
“…[9] e peak incidence of FNMVs occurs between 30 and 60 years of age slightly more common in females. [6] Most commonly, lesions are reported to be centered on the GG with patients presenting with both progressive and sudden facial paralysis and spasm. [16] Other symptoms include conductive hearing loss, otalgia, pulsatile tinnitus, aural bleeding, and vertigo.…”
Section: Discussionmentioning
confidence: 99%
“…[8] It has been suggested that the presence of calcification effectively excludes schwannoma from the diagnosis. [6]…”
Section: Discussionmentioning
confidence: 99%
“…The more common FN schwannoma may compress the nerve and cause dysfunction, whereas a venous malformation may directly infiltrate the nerve and/or cause a vascular steal phenomenon. 39 Therefore, symptoms such as facial paresis or hemifacial spasm or both are much more common with FN IOVMs than the more prevalent schwannoma. When compared with facial neuritis such as Bell palsy, FN dysfunction in IOVMs is more insidious and progressive and will not spontaneously resolve.…”
Section: Facial Nervementioning
confidence: 99%
“…There is a rarer occurrence elsewhere along the FN, namely at the internal auditory canal or second genu. 39 FN IOVMs often infiltrate beyond the margins of the FN canal and geniculate ganglion, aiding in discrimination from facial nerve schwannoma.…”
Section: Facial Nervementioning
confidence: 99%